Degeneration, decadence and disease in the Russian fin de siècle : neurasthenia in the life and work of Leonid Andrew - White, Frederick H., 1970- (Durham modern language series., 2014)
This study demonstrates the implications of scientific discourse on Russian concepts of mental illness and national health. It examines the concept of pathology in Russia, the influence of European medical discourse, the development of Russian psychiatry, and the role that it had on popular culture by investigating the life and works of Leonid Andreev.